Dynamic behavior of a direct expansion evaporator under frosting condition. Part I. Distributed model - TSO, C; CHENG, Y; LAI, A (2006)
A general distributed model with two-phase flow for refrigerant coupled with a frost model is developed for studying the dynamic behavior of an evaporator. The equations are derived in non-steady-state manner for the refrigerant and a quasi-steady state model with permeation for the frost. The complex flow and geometry of the finned tube evaporator lead to uneven wall and air temperature distributions, which in turn affect the rate of frost growth and densification along the coil depth. Results include frost accumulation and its effect on energy transfer, air off-coil temperature, refrigerant liquid dry-out position and propagation of frost fort-nation along the coil. (c) 2005 Elsevier Ltd and IIR. All rights reserved.